2005
DOI: 10.17221/3780-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy effects on frost tolerance and winter survival of garden pansy genotypes

Abstract: Pansies (Viola × wittrockiana Gams) are a commercially important ornamental plant, grown and marketed during autumn and spring (ADAMS et al. 1997).Two hexadecaploid (16x) genotypes were obtained by induced polyploidy in octoploid garden pansy cultivars (AJALIN et al. 2002). The hexadecaploids were selfed in advanced generations (LAGIBO, KOB-ZA 2004a,b) and used also for further breeding in order to exploit the induced desirable traits such as improved compactness and general vigour effect in plant height and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…In Vicia villosa Tulay, Unal [30] observed more chlorophyll in tetraploids. Similar results were reported for black wattle [31], watermelon [32] and garden pansy [33]. By contrast, in Atriplex confertifolia chlorophyll content did not change at various levels of ploidy [34].…”
supporting
confidence: 86%
“…In Vicia villosa Tulay, Unal [30] observed more chlorophyll in tetraploids. Similar results were reported for black wattle [31], watermelon [32] and garden pansy [33]. By contrast, in Atriplex confertifolia chlorophyll content did not change at various levels of ploidy [34].…”
supporting
confidence: 86%
“…Viola •wittrockiana Gams ex Kappert., known as garden pansy, is one of the most common bedding plants worldwide, exhibiting rich flower colors, cold tolerance, and other charming characteristics, such as odor and taste (Fernandes et al, 2017;Lagibo et al, 2005;Li et al, 2014, and literature cited therein). This species is also studied as a promising source of natural antioxidants (Vukics et al, 2008).…”
mentioning
confidence: 99%
“…New pansy varieties with different colors, such as shades of pink, rose, or orange, and unusual bicolor designs have been introduced and are available to gardeners. Studies using a simple selection method to reduce the ploidy level by crossing with diploids to improve uniformity, as well as an increase of polyploidy by mutagenesis to maximize plant morphologic and physiologic characters, have already been performed (Dalbato et al, 2013;Kroon, 1972;Lagibo et al, 2005). Lagibo et al (2005) demonstrated the positive influence of increased polyploid level on frost tolerance and winter survival of garden pansy.…”
mentioning
confidence: 99%
“…Quando é feita a correlação entre SCMR e LA, há uma diferença nos resultados, aproximando-os do que é visto para os materiais cultivados, pois folhas mais espessas geralmente têm densidade mais elevada de clorofila por unidade de área foliar e, portanto, têm uma maior capacidade fotossintética quando comparadas com folhas mais delgadas (Warner et al, 1987). Resultado similar também foi observado por Warner et al (1987) (Lagibo et al, 2005). De acordo com os resultados podemos inferir que, de maneira geral, SCMR e clorofila total aumentam juntas em direção ao maior nível de ploidia, apresentando uma mesma tendência diante da tetraploidização, além de combinar genótipos mais tolerantes com melhores características estéticas (Lagibo et al, 2005).…”
Section: Medidas De Pigmentos Foliaresunclassified
“…Resultado similar também foi observado por Warner et al (1987) (Lagibo et al, 2005). De acordo com os resultados podemos inferir que, de maneira geral, SCMR e clorofila total aumentam juntas em direção ao maior nível de ploidia, apresentando uma mesma tendência diante da tetraploidização, além de combinar genótipos mais tolerantes com melhores características estéticas (Lagibo et al, 2005).…”
Section: Medidas De Pigmentos Foliaresunclassified